A previously unreported variant of the synostotic sagittal suture: Case report and review of salient literature - Madison Budinich; Brittni Burgess; Christian Fisahn; Rod J. Oskouian; R. Shane Tubbs; Elias Rizk (Elsevier, 2016)
Introduction: Sagittal synostosis is a rare congenital disease caused by the premature fusion of the sagittal suture. Craniosynostosis occurs for a variety of reasons, different for every case, and often the etiology is unclear but the anomaly can frequently be seen as part of Crouzon's or Apert's syndromes. Herein, we discuss a rare case of craniosynostosis where the patient presented with a, to our knowledge, a previously undescribed variant of sagittal synostosis. Case report: A 3-month-old female infant presented to a craniofacial clinic for a consultation regarding an abnormal head shape. Images of the skull were performed, demonstrating that the patient had craniosynostosis. The patient displayed no other significant symptoms besides abnormalities in head shape. The sagittal suture was found to extend into the occipital bone where it was synostotic. Conclusion: To our knowledge, a synostotic sagittal suture has not been reported that extended posteriorly it involve the occipital bone. Those who interpret imaging or operate on this part of the skull should consider such a variation. Keywords: Anatomy, Craniosynostosis, Skull, Malformation, Pediatrics